Competing in hot conditions at the Tokyo Olympic Games: Preparation strategies used by Australian race walkers - Carr, A. J.; Vallance, B. S.; Rothwell, J.; Rea, A. E.; Burke, L. M.; Guy, J. H. (Frontiers in Physiology, 2022)
Introduction: The Tokyo 2021 Olympic Games was anticipated to expose athletes to the most challenging climatic conditions experienced in the history of the modern Olympic Games. This study documents strategies executed by Australian endurance athletes during the team holding camp and Olympic Games experiences, including (1) baseline physiological data, training data, and heat acclimation/acclimatization practices; (2) pre- and in-race cooling and nutritional strategies, and (3) Olympic Games race performance data.